2021
DOI: 10.2147/ijn.s305676
|View full text |Cite
|
Sign up to set email alerts
|

Size-Dependent Cytotoxicity and Reactive Oxygen Species of Cerium Oxide Nanoparticles in Human Retinal Pigment Epithelia Cells

Abstract: Purpose The use of cerium oxide nanoparticles (CeO 2 NPs), a lanthanide element oxide and bivalent compound, has been growing continuously in industry and biomedicine. Due to their wide application, the potential human health problems of CeO 2 NPs have attracted attention, but studies on the toxicity of this compound to human eyes are lacking. This study investigated the cytotoxicity and reactive oxygen species (ROS) of CeO 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…Cellular ATP levels were calculated by comparing the luminescence intensity of the treated cells to that of the vehicle control. The cytotoxicity of SiO 2 NPs was assessed using the LDH Release Assay (Beyotime, Beijing, China) as our previous method [ 34 ]. The absorbance was detected at a wavelength of 490 nm by using a Synergy H4 Hybrid microplate reader and data are presented as relative values compared to control.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Cellular ATP levels were calculated by comparing the luminescence intensity of the treated cells to that of the vehicle control. The cytotoxicity of SiO 2 NPs was assessed using the LDH Release Assay (Beyotime, Beijing, China) as our previous method [ 34 ]. The absorbance was detected at a wavelength of 490 nm by using a Synergy H4 Hybrid microplate reader and data are presented as relative values compared to control.…”
Section: Methodsmentioning
confidence: 99%
“…The SiO 2 NP-induced changes in mitochondrial membrane potential were assessed as previously described [ 34 ]. Briefly, R28 cells were seeded in dishes at a density of 1 × 10 5 cells/mL and cultured overnight.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…CeO 2 -NPs, as described above, have excellent antioxidant stress effects and have been shown to reduce photoinduced retinal degeneration. However, a recent study has shown that CeO 2 -NPs exerted toxic effects on human RPE cells (Ma, Li et al, 2021). The study showed that 15 nm CeO 2 -NPs at the concentration of 25 μg/ml reduced the viability of ARPE-19 cells, induced excessive ROS production, and caused mitochondrial dysfunction (Ma, Li et al, 2021).…”
Section: Cerium Oxide Nanoparticlesmentioning
confidence: 99%
“…However, a recent study has shown that CeO 2 -NPs exerted toxic effects on human RPE cells (Ma, Li et al, 2021). The study showed that 15 nm CeO 2 -NPs at the concentration of 25 μg/ml reduced the viability of ARPE-19 cells, induced excessive ROS production, and caused mitochondrial dysfunction (Ma, Li et al, 2021). In addition, the toxicity of CeO 2 -NPs coated with modified ethylene glycol (EGCNPs) on human lens epithelial cells also was evaluated by Hanafy et al (Hanafy, Cave et al, 2020).…”
Section: Cerium Oxide Nanoparticlesmentioning
confidence: 99%